ANALYSIS OF THE EFFECT OF RETURN ON ASSET, DEBT TO EQUITY RATIO, AND TOTAL ASSET TURNOVER ON SHARE RETURN - Kurniawan, Andrie (Journal of Industrial Engineering & Management Research, 2021)
The objectives of this study are to test the effect of the Debt to Equity Ratio (DER), Return On Assets (ROA) and Total Asset Turnover (TATO) on stock returns in Property and Real Estate companies on the IDX. The population in this study were all property and real estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) which are listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period as many as 54 companies. The method used by the author in analyzing the data in this study is descriptive and quantitative statistical analysis with panel data regression, the data is processed with e-views 10. The results showed that partially Return on Assets had no significant effect on Stock Returns, the partial debt to Equty Ratio had no significant effect on Stock Returns, Total Asset Turnover partially had a positive and significant effect on Stock Returns.